A novel mouse model of ischemic carotid artery disease. - Yorito Hattori (Public Library of Science (PLoS), 2014)
Background Carotid artery occlusive disease gradually develops over time, eventually leading to cerebral infarction and high mortality rate. Animal models replicating cerebral infarction resulting from carotid artery occlusive disease have thus been developed to test potential novel treatments, which could be subsequently administered clinically. Methods Adult C57BL/6J male mice were subjected to ameroid constrictor (AC) placement to gradually narrow the bilateral common carotid arteries. Cerebral blood flow (CBF) was measured at several time points. At 7 and 28 days post-operation, post-mortem brain samples were analyzed for ischemic changes. Results The mortality rate was 58.8% at 28 days post-operation. Surviving mice with AC showed continuous reduction of CBF by up to 70% of the baseline level at 28 days. Most of the mice (75%) showed multiple cerebral infarctions in the gray and white matter. Non-surviving mice showed critical CBF reduction below 20-30% of the baseline level before death. Conclusion The application of the AC on the bilateral common carotid arteries in mice could offer a reliable model of severe cerebrovascular insufficiency due to carotid artery occlusive disease and may thus be useful in exploring pharmacological intervention in stroke through monitoring survival rate, infarct formation, and CBF profile.